Predictive value of cerebroplacental ratio measured by Doppler ultrasound for neonatal outcomes in hypertensive disorders of pregnancy: a prospective observational study - Rao, Niharika; Saxena, Rashmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Hypertensive disorders of pregnancy (HDP) are among the most significant contributors to maternal and perinatal morbidity and mortality. Inadequate placental perfusion and foetal hypoxia are key mechanisms affecting fetal growth. The cerebroplacental ratio (CPR), derived from Doppler ultrasound of the middle cerebral artery (MCA) and umbilical artery (UA), is a non-invasive method to assess foetal well-being. This study evaluated the CPR as a predictive tool for adverse neonatal outcomes in HDP. Methods: A prospective observational study was conducted at Saraswathi Institute of Medical Sciences, including 160 singleton pregnancies complicated by HDP beyond 32 weeks of gestation. All participants underwent Doppler velocimetry to assess CPR and were divided into group A (CPR≥1.0) and group B (CPR<1.0). Outcomes assessed included birth weight, Apgar score, NICU admission, and mode of delivery. Statistical analysis involved chi-square tests and sensitivity/specificity calculations. Results: CPR<1.0 was significantly associated with higher caesarean section rates (80% versus 40%), low birth weight (<2500 gm in 67.5% versus 28.8%), low Apgar scores (<7 in 68.8% versus 25%), and increased NICU admissions (72.5% versus 28.8%). CPR showed high specificity but moderate sensitivity for predicting poor outcomes. Conclusions: CPR is a valuable Doppler parameter that can aid in identifying foetuses at risk in hypertensive pregnancies, enabling timely intervention to improve perinatal outcomes.